2017
DOI: 10.1038/s41598-017-16823-2
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo longitudinal imaging of microvascular changes in irradiated oral mucosa of radiotherapy cancer patients using optical coherence tomography

Abstract: Mucositis is the limiting toxicity of radio(chemo)therapy of head and neck cancer. Diagnostics, prophylaxis and correction of this condition demand new accurate and objective approaches. Here we report on an in vivo longitudinal monitoring of the oral mucosa dynamics in 25 patients during the course of radiotherapy of oropharyngeal and nasopharyngeal cancer using multifunctional optical coherence tomography (OCT). A spectral domain OCT system with a specially-designed oral imaging probe was used. Microvasculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…20,40,42,43 Some studies used functional OCT microvascular imaging for radiobiological monitoring of different radiation dose levels in pancreatic human tumor xenografts 47 and in head and neck cancer using multifunctional OCT in a clinical pilot study in patients. 48 Moreover, there are pilot patient studies reported on using microvascular OCT imaging with developed oral imaging probes to monitor late oral radiation-induced damages in vivo. 36,49 However, it is unknown whether we can directly compare these findings with dose response of the esophagus in mice.…”
Section: Discussionmentioning
confidence: 99%
“…20,40,42,43 Some studies used functional OCT microvascular imaging for radiobiological monitoring of different radiation dose levels in pancreatic human tumor xenografts 47 and in head and neck cancer using multifunctional OCT in a clinical pilot study in patients. 48 Moreover, there are pilot patient studies reported on using microvascular OCT imaging with developed oral imaging probes to monitor late oral radiation-induced damages in vivo. 36,49 However, it is unknown whether we can directly compare these findings with dose response of the esophagus in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding to the approach of OCT angiography, the grade of tissue vascularization is estimated by measuring the luminal area of larger vessels and relating the result to the avascular epithelial layer (also referred to as mean vessel density) [ 40 , 41 ]. For this, single or multiple yellow-colored elliptic shapes mark regions of vascularization, as shown in Figure 2 c. The sum of the segmented areas is divided by the total area of the detected epithelium determined by a polygonal shape.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…22,23 Similar functional OCT approaches are being investigated for detection, quantification, and management of early RT toxicities as well, for example in intrafraction monitoring of mucositis development in superficial mucosal layers of the oral cavity of head and neck radiotherapy patients. [52][53][54] Further, skin is indeed a very important target of such RT imaging studies, given its clinical importance as a dose-limiting organ and thus common occurrence of RIF. However, its thicker structures in humans compared to mice may somewhat limit clinical utility, as OCT can only detect important RIF changes within ∼1 mm of the skin surface (unless optical clearing is used, a promising practical solution to this obstacle), 55 thus its application should be driven by relevant tissue changes within this depth range.…”
Section: Statisticsmentioning
confidence: 99%